A super-amphiphobic micro-nano composite structure and preparation method thereof

By spin-coating photoresist on the substrate and performing photolithography and element etching, combined with nanoimprinting technology, a micro-nano composite structure with superhydrophobic and superoleophobic properties is prepared, which solves the problem that the prior art is difficult to achieve superoleophobic effects, and improves the simplicity and repeatability of the preparation.

CN114265281BActive Publication Date: 2025-04-22NANJING UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202111527592.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-14
Publication Date
2025-04-22
Estimated Expiration
2041-12-14

AI Technical Summary

Technical Problem

It is difficult to achieve super oleophobic effect in the existing superhydrophobic surfaces, and the regularly arranged microscopic overhang structures have problems such as damage, complex preparation process and poor wear resistance in applications.

Method used

Micropore arrays were prepared by spin-coating photoresist on the substrate and performing photolithography and element etching; then the silica layer was wrapped on the micropore array and the nanostructures were imprinted on the micropore array using nanoimprinting technology to obtain micro-nano composite structures with superhydrophobic and superoleophobic properties.

Benefits of technology

It realizes the micro-nano composite structure with superhydrophobic and superoleophobic properties, and has the advantages of simple operation, short preparation cycle and high repeatability. It is suitable for self-cleaning, anti-corrosion and anti-fouling fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114265281B_ABST
    Figure CN114265281B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of micro-nano processing technology, and provides a super-amphiphobic micro-nano composite structure and a preparation method thereof. The present invention uses photolithography and element etching to prepare a suspended micrometer hole array on the surface of a substrate; and then uses ultraviolet light nanoimprinting technology to imprint a nanostructure on the micrometer hole array to obtain a micro-nano composite structure with super-hydrophobic and super-oleophobic properties. The preparation method provided by the present invention has the advantages of short preparation cycle and high repeatability. The prepared super-amphiphobic micro-nano composite structure has excellent hydrophobicity and oleophobicity, and has broad application prospects in self-cleaning, corrosion resistance and anti-fouling. The data of the embodiment show that the water contact angle of the super-amphiphobic micro-nano composite structure provided by the present invention is 150-162.8°, and the oil contact angle is 150-154.8°.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of micro-nano processing, and in particular to a super-amphiphobic micro-nano composite structure and a preparation method thereof. Background Art

[0002] As a special wettability state, superamphiphobic surface has great application potential in the fields of anti-icing, water-oil separation and self-cleaning. At present, most research focuses on superhydrophobic surfaces. Compared with water with higher surface energy, low surface energy liquids are more likely to be wetted. Therefore, achieving superoleophobic surface is the main difficulty now. Most of the existing research is to structure the surface, and achieve the Cassie state with an air layer by obtaining a low duty cycle and high roughness, so as to achieve the effect of non-wetting of the surface.

[0003] The springtail structure in nature provides inspiration for super-amphiphobic surfaces. The springtail epidermis has a roughly regularly arranged microscopic overhanging structure, which enables the epidermis to form a stable air layer, thus possessing super-liquid-repellent properties. Studies have shown that the introduction of a multi-level overhanging structure can achieve super-liquid-repellent effects on low surface energy liquids such as oil and hexadecane; and the composite nanostructure on the microstructure can quickly obtain a surface with a lower duty cycle. However, the regularly arranged microscopic overhanging structure is limited in practical applications due to the problems of easy surface damage, complex preparation process, and poor wear resistance; traditional methods for obtaining nanostructures include spraying nanoparticles, self-organization, and phase separation, but the above-mentioned nanostructure acquisition methods are complex and have a long preparation process, which limits their application in industrial production. That is, the preparation method of the composite nanostructure of the overhanging structure is cumbersome. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a super-amphiphobic micro-nano composite structure and a preparation method thereof. The preparation method provided by the present invention is simple to operate and obtains a super-amphiphobic micro-nano composite structure.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a super-amphiphobic micro-nano composite structure, comprising the following steps:

[0007] Spin-coating a photoresist on a substrate, attaching a photolithography mask to the surface of the photoresist, and sequentially performing photolithography and element etching to obtain a micrometer hole array;

[0008] Coating a silicon dioxide layer on the surface of the micropore array to obtain a micropore structure;

[0009] Covering the PDMS soft template absorbed with the imprint glue on the micrometer pore structure, performing nanoimprinting, and obtaining a micro-nano composite structure;

[0010] Performing an anti-sticking treatment on the micro-nano composite structure to obtain the super-amphiphobic micro-nano composite structure;

[0011] The photolithography mask has a micrometer array;

[0012] The PDMS soft template has a nanoarray.

[0013] Preferably, the substrate includes a silicon substrate or a carbon substrate.

[0014] Preferably, when the substrate is a silicon substrate, the etching gas for the element etching includes SF6, and the protective gas includes C4F8.

[0015] Preferably, the photoresist includes S1813 photoresist or AZ5214 photoresist.

[0016] Preferably, the shape of the micrometer array includes square, circle or isosceles trapezoid; the size of the micrometer array is 30 μm to 150 μm; and the duty cycle of the photolithography mask is 9 to 15%.

[0017] Preferably, the height of the element etching is 4-9 μm.

[0018] Preferably, the silicon dioxide layer has a thickness of 15 to 30 nm.

[0019] Preferably, the method for preparing the PDMS soft template absorbed with embossing glue comprises:

[0020] The blank substrate is spin-coated with embossing glue, and the PDMS soft template is naturally covered on the embossing glue to absorb the glue, so as to obtain the PDMS soft template absorbing the embossing glue.

[0021] Preferably, the nanoarray is a cylindrical array with a diameter of 100 to 400 nm, a height of 200 to 500 nm, and a period of 300 to 800 nm.

[0022] The present invention also provides a super-amphiphobic micro-nano composite structure obtained by the preparation method described in the above technical solution, with a water contact angle of 150 to 162.8° and an oil contact angle of 150 to 154.8°.

[0023] The present invention provides a method for preparing a super-amphiphobic micro-nano composite structure, comprising the following steps: spin coating a photoresist on a substrate, attaching a photolithography mask to the surface of the photoresist, sequentially performing photolithography and element etching to obtain a micrometer hole array; wrapping a silicon dioxide layer on the surface of the micrometer hole array to obtain a micrometer hole structure; covering the micrometer hole structure with a PDMS soft template that absorbs an imprinting glue, performing nanoimprinting to obtain a micrometer hole structure; performing anti-adhesion treatment on the micrometer hole structure to obtain a super-amphiphobic micrometer hole composite structure; the photolithography mask has a micrometer array; the PDMS soft template has a nanometer array. The present invention utilizes photolithography and element etching to prepare a suspended micrometer hole array on the surface of a substrate; and then using nanoimprinting technology to imprint a nanostructure on the micrometer hole array to obtain a micrometer hole array with super-hydrophobic and super-oleophobic properties. The preparation method provided by the present invention has the advantages of short preparation cycle and high repeatability, and has broad application prospects in self-cleaning, corrosion prevention and anti-fouling.

[0024] The present invention also provides a super-amphiphobic micro-nano composite structure obtained by the preparation method described in the above technical solution. The super-amphiphobic micro-nano composite structure provided by the present invention has excellent hydrophobicity and oleophobicity.

[0025] The data of the examples show that the water contact angle of the super-amphiphobic micro-nano composite structure provided by the present invention is 150-162.8°, and the oil contact angle is 150-154.8°. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The present invention provides a flow chart of the preparation method of the super-amphiphobic micro-nano composite structure, wherein (a) is the preparation of a micron pore structure, (b) is the preparation of a PDMS soft template absorbing an imprinting glue; (c) is the process of preparing a micro-nano composite structure by nanoimprinting; wherein: a-1 is a substrate, a-2 is a photoresist, a-3 is a silicon dioxide layer; b-1 is a blank substrate, b-2 is an imprinting glue, and b-3 is a PDMS soft template;

[0027] Figure 2 This is a SEM plan view of the super-amphiphobic micro-nano composite structure obtained in Example 1;

[0028] Figure 3 The test diagram of the contact angles of water and oil of the super-amphiphobic micro-nano composite structure obtained in Example 1;

[0029] Figure 4 This is a SEM plan view of the super-amphiphobic micro-nano composite structure obtained in Example 2;

[0030] Figure 5 This is a test diagram of the contact angles of water and oil of the super-amphiphobic micro-nano composite structure obtained in Example 2. DETAILED DESCRIPTION

[0031] The present invention provides a method for preparing a super-amphiphobic micro-nano composite structure, comprising the following steps:

[0032] Spin-coating a photoresist on a substrate, attaching a photolithography mask to the surface of the photoresist, and sequentially performing photolithography and element etching to obtain a micrometer hole array;

[0033] Coating a silicon dioxide layer on the surface of the micropore array to obtain a micropore structure;

[0034] Covering the PDMS soft template absorbed with the imprint glue on the micrometer pore structure, performing nanoimprinting, and obtaining a micro-nano composite structure;

[0035] Performing an anti-sticking treatment on the micro-nano composite structure to obtain the super-amphiphobic micro-nano composite structure;

[0036] The photolithography mask has a micrometer array;

[0037] The PDMS soft template has a nanoarray.

[0038] In the present invention, unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.

[0039] The invention spin-coats photoresist on a substrate, attaches a photolithography mask to the surface of the photoresist, and sequentially performs photolithography and element etching to obtain a micrometer hole array.

[0040] In the present invention, the substrate preferably includes a silicon substrate or a carbon substrate, and more preferably a silicon substrate.

[0041] In the present invention, the photoresist preferably includes S1813 photoresist or AZ5214 photoresist, and more preferably S1813 photoresist. In the present invention, the rotation speed of the spin coating of the photoresist is preferably 3000r / s to 5000r / s, and more preferably 4000r / s; the spin coating time is preferably 40 to 50s, and more preferably 45s. In the present invention, the thickness of the photoresist is preferably 1.5 to 1.6μm.

[0042] In the present invention, the photolithography mask has a micrometer array. In the present invention, the shape of the micrometer array preferably includes a square, a circle or an isosceles trapezoid; the size of the micrometer array is preferably 30 μm to 150 μm. In the present invention, the duty cycle of the photolithography mask is preferably 9 to 15%, and more preferably 10 to 14%.

[0043] In the present invention, the height of the element etching is preferably 4 to 9 μm.

[0044] In the present invention, when the substrate is a silicon substrate, the etching gas for the element etching preferably includes SF6, and the protective gas preferably includes C4F8.

[0045] In the present invention, the element etching preferably uses a photoresist obtained by photolithography as a mask.

[0046] After obtaining the micrometer hole array, the present invention coats the surface of the micrometer hole array with a silicon dioxide layer to obtain a micrometer hole structure.

[0047] In the present invention, the thickness of the silicon dioxide layer is preferably 15 to 30 nm, and more preferably 20 to 25 nm.

[0048] In the present invention, the encapsulated silicon dioxide layer is preferably obtained by plasma enhanced chemical vapor deposition or electron beam evaporation. The present invention does not specifically limit the parameters of the plasma enhanced chemical vapor deposition or electron beam evaporation method, as long as a silicon dioxide layer with a thickness of 15 to 30 nm can be obtained.

[0049] In the present invention, the micron pore structure has an overhanging structure; the overhanging structure refers to a "T"-shaped structure at the raised edge when viewed from a cross section.

[0050] After the micrometer pore structure is obtained, the present invention covers the PDMS soft template absorbed with the imprint glue on the micrometer pore structure, performs nanoimprinting, and obtains a micro-nano composite structure.

[0051] In the present invention, the method for obtaining the PDMS soft template absorbed with the embossing glue preferably includes:

[0052] The blank substrate is spin-coated with embossing glue, and the PDMS soft template is naturally covered on the embossing glue to absorb the glue, so as to obtain the PDMS soft template absorbing the embossing glue.

[0053] In the present invention, the blank substrate is preferably a blank silicon substrate.

[0054] In the present invention, the embossing adhesive is preferably a UV-curable embossing adhesive; the UV-curable embossing adhesive preferably includes CN975 UV nano-embossing adhesive. In the present invention, the spin coating speed of the embossing adhesive is preferably 3000-4000 r / s, the time is preferably 40-45 s; the thickness of the embossing adhesive is preferably 100-300 nm.

[0055] In the present invention, the PDMS soft template is preferably obtained by pouring PDMS in a silicon master template.

[0056] In the present invention, the PDMS soft template has a nanoarray; the nanoarray is preferably a cylindrical array with a diameter of 100 to 400 nm, a height of 200 to 500 nm, and a period of 300 to 800 nm.

[0057] In the present invention, the glue suction time is preferably 10s to 30s.

[0058] In the present invention, the nano-imprinting preferably comprises: covering the PDMS soft template absorbed with the imprinting glue on the micrometer pore structure, passing nitrogen gas, and performing nano-imprinting.

[0059] In the present invention, the nitrogen gas flow time is preferably 2 to 3 minutes. In the present invention, when the imprint adhesive is preferably a UV-curable imprint adhesive, the nanoimprint is preferably UV nanoimprint; the UV nanoimprint is preferably UV exposure; and the UV exposure time is preferably 10 to 11 minutes.

[0060] After the nano-imprinting, the present invention preferably further comprises peeling off the PDMS soft template.

[0061] After obtaining the micro-nano composite structure, the present invention performs anti-sticking treatment on the micro-nano composite structure to obtain the super-amphiphobic micro-nano composite structure.

[0062] In the present invention, the anti-sticking treatment preferably includes coating the surface of the micro-nano composite structure with silicon dioxide, followed by ozone treatment and steam treatment.

[0063] In the present invention, the thickness of the silicon dioxide layer is preferably 15 to 30 nm; the encapsulated silicon dioxide layer is preferably obtained by plasma enhanced chemical vapor deposition or electron beam evaporation. The present invention does not specifically limit the parameters of the plasma enhanced chemical vapor deposition or electron beam evaporation method, as long as a silicon dioxide layer with a thickness of 15 to 30 nm can be obtained.

[0064] In the present invention, the ozone treatment time is preferably 30 to 60 minutes. In the present invention, the ozone treatment can form hydroxyl groups on the surface of the micro-nano composite structure.

[0065] In the present invention, the steam of the steam treatment preferably includes perfluoroalkyl chlorosilane steam; the temperature of the steam treatment is preferably 80 to 95° C.; the time of the steam treatment is preferably 2 to 3 hours. In the present invention, the steam treatment is preferably carried out in an oven.

[0066] After the steam treatment is completed, the present invention preferably further comprises allowing the product obtained by the steam treatment to stand; the standing temperature is preferably 15° C. to 25° C., and the standing time is preferably 17 to 18 hours.

[0067] In the present invention, the perfluoroalkyl chlorosilane in the steam treatment can self-assemble with the hydroxyl groups obtained by hydroxylation to form a release layer.

[0068] Figure 1The present invention provides a flow chart of a method for preparing a super-amphiphobic micro-nano composite structure; wherein (a) is the preparation of a micrometer pore structure, (b) is the preparation of a PDMS soft template absorbed with an imprinting glue; (c) is a process for preparing a micro-nano composite structure by nanoimprinting; wherein: a-1 is a substrate, a-2 is a photoresist, a-3 is a silicon dioxide layer; b-1 is a blank substrate, b-2 is an imprinting glue, and b-3 is a PDMS soft template.

[0069] The present invention also provides a super-amphiphobic micro-nano composite structure obtained by the preparation method described in the above technical solution. The super-amphiphobic micro-nano composite structure provided by the present invention has a water contact angle of 150-162.8° and an oil contact angle of 150-154.8°.

[0070] Since the super-amphiphobic micro-nano composite structure provided by the present invention has excellent super-amphiphobicity, it can be used in the fields of self-cleaning, corrosion prevention and anti-fouling.

[0071] The super-amphiphobic micro-nano composite structure and the preparation method thereof provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0072] Example 1

[0073] In this embodiment, the <100> , P-type single-sided polished silicon wafer is used as the substrate, and the specific preparation process and parameters are as follows:

[0074] 1. Preparation of micrometer hole structure: Spin-coat photoresist S1813 on silicon wafer at a rate of 4000 r / s for 40 seconds to obtain a photoresist layer with a thickness of 1.5 μm; Take a square photolithography mask with a side length of 33 μm and a period of 35 μm for photolithography to obtain a photoresist square micrometer hole array with a side length of 33 μm and a period of 35 μm; Use the photoresist as a mask to perform deep silicon etching, the etching gas is SF6, and the protective gas is C4F8, to obtain a square hole depth of 5.5 μm, and obtain a micrometer square hole structure with a pendant shape, and then use plasma enhanced chemical vapor deposition (PECVD, PlasmalabSystem 80Plus) to deposit a SiO2 layer with a thickness of 25 nm on the surface of the micrometer square hole.

[0075] 2. Micro-nano composite structure: A PDMS soft template was cast using a silicon master template. The nanoarray of the PDMS soft template was a cylindrical array with a diameter of 300nm, a height of 300nm, and a period of 600nm. A CN975 UV nanoimprint glue with a thickness of 200nm was spin-coated on a blank silicon wafer at a speed of 3000r / s for 40s. The PDMS soft template was naturally covered on the imprint glue and the glue was absorbed for 15s. The PDMS soft template after the glue absorption was then covered on the structure of the micrometer hole array prepared in the previous step. Nitrogen was passed through for 2min, and UV exposure treatment was performed in a nitrogen atmosphere for 10min. The PDMS soft template was opened to form a composite micrometer column array on the micrometer hole array.

[0076] 3. Anti-sticking treatment: A 20 nm SiO2 layer was deposited on the surface of the micro-nano composite structure by plasma enhanced chemical vapor deposition; the surface was treated with ozone for 40 min, and then steamed with perfluoroalkyl chlorosilane vapor in a vacuum oven, allowed to stand at 85°C for 2 h, and then allowed to stand for 17 h to restore it to the surface of the sample, thereby obtaining a super-amphiphobic micro-nano composite structure.

[0077] Figure 2 This is the SEM plan view of the obtained super-amphiphobic micro-nano composite structure.

[0078] Figure 3 The test diagram of the water and oil contact angles of the obtained super-amphiphobic micro-nano composite structure is as follows: the water contact angle (WCA) of the obtained super-amphiphobic micro-nano composite structure is 159.4°, and the oil contact angle (OCA) is 152.7°.

[0079] Example 2

[0080] In this embodiment, the <100> , P-type single-sided polished silicon wafer is used as the substrate, and the specific preparation process and parameters are as follows:

[0081] 1. Preparation of micrometer hole structure: Spin-coat photoresist S1813 on silicon wafer at a rate of 4500 r / s for 40 s to obtain a photoresist layer with a thickness of 1.5 μm; Take a photolithography mask with a circular array of 57 μm in diameter and 59 μm in period for photolithography to obtain a photoresist circular micrometer hole array with a circular diameter of 57 μm and a period of 59 μm; Use the photoresist as a mask for deep silicon etching, the etching gas is SF6, the protective gas is C4F8, and the circular hole depth is 5 μm, and a micrometer circular hole structure with a pendant shape is obtained, and then a SiO2 layer with a thickness of 2 nm is deposited on the surface of the micrometer square hole by plasma enhanced chemical vapor deposition (PECVD, PlasmalabSystem80Plus).

[0082] 2. Micro-nano composite structure: A PDMS soft template was cast using a silicon master template. The nanoarray of the PDMS soft template was a cylindrical array with a diameter of 300nm, a height of 300nm, and a period of 600nm. A 240nm thick CN975 imprint glue was spin-coated on an empty silicon wafer at a speed of 3000r / s for 40s. The PDMS soft template was naturally covered on the imprint glue and the glue was absorbed for 20s. The PDMS soft template after the glue absorption was then covered on the structure of the micrometer hole array prepared in the previous step. Nitrogen was passed through for 2min, and then UV exposure was performed in a nitrogen atmosphere for 10min. The PDMS was lifted to form a composite micrometer column array on the micrometer hole array.

[0083] 3. Anti-sticking treatment: 20 nm SiO2 was plated on the surface of the micro-nano composite structure by plasma enhanced chemical vapor deposition; it was treated with ozone for 60 minutes, and then steamed with perfluoroalkyl chlorosilane vapor in a vacuum oven, allowed to stand at 80°C for 2 hours, and then allowed to stand for 18 hours to recover to the sample, thereby obtaining a super-amphiphobic micro-nano composite structure.

[0084] Figure 4 This is the SEM plan view of the obtained super-amphiphobic micro-nano composite structure.

[0085] Figure 5 The test diagram of the water and oil contact angles of the obtained super-amphiphobic micro-nano composite structure; the results are: the water contact angle (WCA) of the obtained super-amphiphobic micro-nano composite structure is 162.8°, and the oil contact angle (OCA) is 154.8°.

[0086] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a super-amphiphobic micro-nano composite structure, comprising the following steps: Spin-coating a photoresist on a substrate, attaching a photolithography mask to the surface of the photoresist, and sequentially performing photolithography and element etching to obtain a micrometer hole array; Coating a silicon dioxide layer on the surface of the micropore array to obtain a micropore structure; Covering the PDMS soft template absorbed with the imprint glue on the micrometer pore structure, performing nanoimprinting, and obtaining a micro-nano composite structure; Performing an anti-sticking treatment on the micro-nano composite structure to obtain the super-amphiphobic micro-nano composite structure; The photolithography mask has a micrometer array; The PDMS soft template has a nanoarray; The shape of the micrometer array includes square, circle or isosceles trapezoid; the size of the micrometer array is 30 μm to 150 μm; the duty cycle of the photolithography mask is 9 to 15%; The height of the element etching is 4 to 9 μm; The thickness of the silicon dioxide layer is 15 to 30 nm; The method for preparing the PDMS soft template absorbed with the embossing glue comprises: Spin-coating the embossing glue on a blank substrate, and naturally covering the PDMS soft template on the embossing glue to absorb the glue, thereby obtaining the PDMS soft template absorbing the embossing glue; The nanometer array is a cylindrical array with a diameter of 100-400nm, a height of 200-500nm and a period of 300-800nm.

2. The preparation method according to claim 1, characterized in that: The substrate includes a silicon substrate or a carbon substrate.

3. The preparation method according to claim 2, characterized in that: When the substrate is a silicon substrate, the etching gas for the element etching includes SF6, and the protective gas includes C4F8.

4. The preparation method according to claim 1, characterized in that: The photoresist includes S1813 photoresist or AZ5214 photoresist.

5. The super-amphiphobic micro-nano composite structure obtained by the preparation method according to any one of claims 1 to 4, characterized in that: The water contact angle of the super-amphiphobic micro-nano composite structure is 150-162.8°, and the oil contact angle is 150-154.8°.

Citation Information

Patent Citations

  • Preparation method of composite concave angle micron structure with super-amphiphobic property

    CN112624032A